Academic research into marketing: Many publications, but little impact? - Tim Hughes; Merlin Stone; Eleni Aravopoulou; Len Tiu Wright; Liz Machtynger (Cogent Business & Management, 2018)
This article reviews some issues associated with the way in which academic research into marketing is evaluated by UK education authorities using their research excellence framework (REF), in particular the impact component of the assessment. It discusses the extent to which research by marketing academics published in leading academic journals is relevant to the concerns of marketing management and how this relevance or lack of it may be reflected in the relative paucity of impact submissions in marketing. It considers the model of impact assessment used in the REF and how this differs from how marketing academics work in practice, giving three examples of significant impact that would not be acceptable under current rules. It concludes by suggesting that alternative models for impact should be investigated and suggests that using more practical models might result in better engagement of marketing academics with business, leading to greater relevance in teaching and employability of marketing graduates.
Keywords: 650